We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
132
1
avatar

2 (x-3)^2 + 1 = 9 

 Dec 10, 2018

Best Answer 

 #1
avatar+18439 
+2

2 (x-3)^2 + 1 = 9    Subtract 1 from both sides of the equation

2(x-3)^2 = 8          Divide both sides by 2

(x-3)^2 = 4             SQRT both sides

x-3 = +-2           Add 3 to both sides

x = 5 or 1 

 Dec 10, 2018
 #1
avatar+18439 
+2
Best Answer

2 (x-3)^2 + 1 = 9    Subtract 1 from both sides of the equation

2(x-3)^2 = 8          Divide both sides by 2

(x-3)^2 = 4             SQRT both sides

x-3 = +-2           Add 3 to both sides

x = 5 or 1 

ElectricPavlov Dec 10, 2018

13 Online Users

avatar
avatar
avatar